Effet épigénétique sur la génétique de faisan commun (Phasianus colchicus.L, 1758) - Hocini, Fatima Zohra (My University, 2016)
The common pheasant raised and controlled at the Centre of Zeralda Hunting belongs to the order Galliformes, family Phasianidae and gender Phasianus. It was introduced in Algeria in 1970. We operate how epigenetics has an effect on the development of chicks. The results of this test have shown that there has a hatching rate of decline in egg placed in the refrigerator by supplying fresh eggs but embryonic mortality rate is quite strong in the first eggs. Even the weight of pheasants after hatching is used to analyze the influence of temperature. So phenotypic variability on production parameters such as weight, fertility rate and mortality rate shows that the common pheasant population is influenced by temperature especially during egg incubation and development at the time of chicks pheasants This confirms that lower temperature has a negative effect on the eggs of pheasant and young pheasants in different stages of their growth.
Keywords: common pheasant; epigenetics; phenotypic variability; the fertility rate; mortality rate and incubation.; le faisan commun; l’épigénétique; la variabilité phénotypique; le taux de fertilité; taux de mortalité et l’incubation